THE RELATIONSHIP BETWEEN HEALTH LITERACY AND HEALTH PROMOTING DISEASE PREVENTING BEHAVIORS, AMONG PEOPLE WHO HAVE PREVIOUSLY BEEN INFECTED WITH COVID-19, IN THEPHARAK DISTRICT, NAKHON RATCHASIMA PROVINCE - ปืนกระโทก ประภาส; เพชรมณี สาโรจน์; ปัญญาใสโสภณ ธณกร (Primary Health Care Journal (Northeastern Edition), 2024)
This cross-sectional descriptive study aims to examine the relationship between health literacy and health promoting and disease preventive behaviors among people who have previously contracted COVID-19. The research sample consisted of 280 people selected through simple random sampling. The research tools included a self-developed health literacy questionnaire and a health promoting and disease preventive behaviors questionnaire, validated by three experts, with item-objective congruence (IOC) values ranging from 0.66 to 1.00 and reliability coefficients ranging from 0.77 to 0.97. Data were analyzed using statistics including frequency, percentage, mean, standard deviation, chi-square tests, and Pearson correlation coefficients. The findings were as follows: 1) Occupation, income, quarantine duration, and vaccination status were significantly related to health promoting and disease preventive behaviors regarding COVID-19 at a 0.05 significance level. 2) Health literacy in terms of access skill, communication skill, self-management skill, and media literacy skill was positively correlated with health promoting and disease preventive behaviors at .05 significance level. And 3) Health literacy in terms of cognitive skill was negatively correlated with health-promoting and disease-preventive behaviors at .05 significance level.